Effects of microbial fertilizer and green manure cropping systems on fruit quality of Korla fragrant pear - Ke, Yixin; Li, Jie; He, Zhanyi; Liu, Xiuxiu; Shen, Xing; Chai, Zhongping; Zeng, Maomao (Frontiers in Plant Science, 2025)
Korla Fragrant Pear(Pyrus sinkiangensis Yu), a high-value Geographical Indication product from Xinjiang, China, faces declining fruit quality due to soil degradation from intensive monoculture. This study investigated microbial fertilizer (JF) and green manure (oil sunflower - DK1, DK2; sweet clover - CM1, CM2) intercropping in a pear orchard to improve soil and fruit quality, compared to conventional fertilization (CK). Comprehensive analyses assessed soil properties, fruit minerals, metabolites (monosaccharides, fatty acids, amino acids), and volatile organic compounds (VOCs).Both JF and green manure treatments improved soil physicochemical properties, with CM1 showing the greatest effect. Treatments JF, CM1, CM2, DK1, and DK2 significantly increased fruit K, P, Fe, and Mn content but significantly decreased Zn content. JF significantly enhanced monosaccharide accumulation, while CM1 and high-density oil sunflower (DK2) notably increased fatty acid and free amino acid content. However, all treatments (JF, CM1, CM2, DK1, DK2) significantly reduced total fruit VOCs. Correlation analysis indicated fruit Zn content was positively correlated with most VOCs. Reduced Zn inhibited alcohol dehydrogenase (ADH) and copper-zinc superoxide dismutase (Cu/Zn SOD) activity, leading to decreased VOC synthesis. Therefore, while CM1 is recommended as the optimal strategy for improving basic nutritional quality and soil fertility, coordinated zinc nutrition management is essential when implementing green manure to balance nutritional enhancement with maintaining characteristic flavor, ensuring sustainable industry development.